5.4k views
23 votes
Thanks to anyone who helps!

Thanks to anyone who helps!-example-1
User Gaddy
by
4.4k points

1 Answer

6 votes

Answer:

Explanation:

Look at the determinant.

a = k

b = 1

c = k

sqrt(b^2 - 4*k*k)

sqrt(1 - 4k^2)

The only way this can work out to repeated solutions is if k = +/- 1/2

That way 1 - 4(1/2)^2 = 0 or 1 - 4*(-1/2)^2 = 0

That way both solutions will be

-b / 2a

-1 / 2/(1/2) = - 1

or

-1 / 2(-1/2) = 1

So the answer is k = 1/2, - 1/2

User Vogon Jeltz
by
4.6k points